Germline Human Leukocyte Antigen Status is Associated With Immunotherapy-Induced Pneumonitis and Treatment Response in Patients With Non–Small Cell Lung Cancer With High Programmed Death-Ligand 1 Expression - Alvin H.K. Cheung, MBBS, PhD; Zeta Mui, MPhil; Walter W. Yeung, PhD; Chit Chow, PhD; Mandy F. Yu, BSc; Olivia H. Chen, MD, PhD; Kit-Yee Wong, MPhil; Fuda Xie, MPhil; Yat Ming Lau, MBBS; Alfred S-L. Cheng, PhD; Wei Kang, PhD; Ka-Fai To, MBChB; et al. (JTO Clinical and Research Reports)
Introduction: The germline human leukocyte antigen (HLA) status has been found to be associated with immunotherapy outcomes in patients with NSCLC, but its correlation to immunotherapy-induced pneumonitis and prognostic impact in the Asian population remains largely unknown. Methods: We evaluated the HLA genotype of the germline and available tumor samples in 42 patients with programmed death-ligand 1 expression of 50% or higher undergoing pembrolizumab immunotherapy. The HLA allele expression was correlated with tumor response, disease survival, and the occurrence of pneumonitis. Results: It was observed that the germline HLA-C homozygosity and HLA-DRB1∗13 expression were related to a worse progression-free survival and treatment response. Importantly, all patients (7/7 patients) who developed pneumonitis in our cohort expressed the HLA-DPB1∗02 allele, and the incidence of pneumonitis was 31.8% (7/22 patients) in patients expressing this allele compared with 0% (0/20 patients) in those without this allele (p = 0.009). Investigation of the tumor samples from 15 patients revealed some degree of HLA loss in the HLA class I loci in 40% (6/15) of patients, and no significant difference in tumor mutation burden was found among patients with different treatment responses. Conclusion: Taken together, this study evaluated the impact of HLA status in both germline and tumor samples in patients with NSCLC with high programmed death-ligand 1 expression, and the high incidence of immunotherapy-induced pneumonitis in patients expressing the HLA-DPB1∗02 allele may suggest a routine HLA typing and closer monitoring in this patient subset.